Who Looks after the Kids? The Effects of Childcare Choice on Early Childhood Development in China. (11th February 2021) - Zhang, Jing; Appleton, Simon; Song, Lina; Liu, Bing
Abstract: This paper examines whether childcare choice affects the early childhood development of children aged 7–59 months. Using the data from Chinese Family Panel Studies, we look at household choices between parental and grandparental cares and the timing of four key early life achievements – walking, talking, counting and toilet training. We conceptualize early childhood development within a household production model, which enables us to identify the impacts of childcare. Our results suggest that compared with parental care, grandparental care delays the achievement of all four outcome measures. Grandparental care is particularly disadvantageous for children who are 'left‐behind' by migrant parents.